Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/1750-3841.15679
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry leaf phenolics and fiber exert anti‐obesity through the gut microbiota‐host metabolism pathway

Abstract: The effect of mulberry leaf powder and components on preventing obesity and regulating lipid metabolism were investigated in the present study. The mechanism of action was explored by examining the gut microbiota and lipid metabolism-related signaling pathways. As evidenced by the nutritional obesity rats model experiments, the middle concentration mulberry leaf powder (MLP) group (0.8 g/kg⋅d) significantly reduced Lee's index (25.1, compared with model control group [MC] 25.7) and had the strongest lipid meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…It was surprising that MLWE supplementation could further increase or decrease the relative abundance of Oscillatoriales_cyanobacterium and Gastranaerophilales in HFHS-fed and STZ-induced mice. According to our results, the modulation by MLWE of the gut microbiota was a sophisticated process and no specific pattern of the changing composition of gut bacterial communities could be obtained, which might be due to the changes of microenvironment nourishing the growth of gut microbiota brought about by the ingredients of MLWE (Hu et al, 2019;Liao, Long, Zou, Liu, & Li, 2021); this should be further investigated at the genus-or species-specific levels.…”
Section: Discussionmentioning
confidence: 75%
“…It was surprising that MLWE supplementation could further increase or decrease the relative abundance of Oscillatoriales_cyanobacterium and Gastranaerophilales in HFHS-fed and STZ-induced mice. According to our results, the modulation by MLWE of the gut microbiota was a sophisticated process and no specific pattern of the changing composition of gut bacterial communities could be obtained, which might be due to the changes of microenvironment nourishing the growth of gut microbiota brought about by the ingredients of MLWE (Hu et al, 2019;Liao, Long, Zou, Liu, & Li, 2021); this should be further investigated at the genus-or species-specific levels.…”
Section: Discussionmentioning
confidence: 75%
“…Another study demonstrated that mulberry leaf flavonoids and its active metabolite quercetin could reduce excessive cholesterol accumulation both in vivo and in vitro, and play a role in lowering blood lipid via decreasing the mRNA and protein expression of SREBP-2 and HMGCR [125]. Likewise, mulberry leaf phenolic and fiber mixture exhibited lipid-lowering effects via reducing the mRNA and proteins expression of FAS, C/EBR-α and PPARγ as well as regulating the gut microbiota [126]. In ethanol-induced liver injury mouse model, mulberry leaf extract and its chlorogenic derivatives improved lipid profiles, attenuated hepatic inflammation and decreased lipid accumulation [127].…”
Section: Mori Folium (Sangye)mentioning
confidence: 99%
“…The sulfate group and gut microbiota played an important role in the regulation of glycolipid metabolism by GLP. Liao, Long, Zou, Liu, & Li (2021) discovered that the reduction of Firmicutes/Bacteroidetes ratio improved the bioaccessibility, bioavailability and lipid metabolism, thus reducing the Lee’s index and perfecting the level of lipid (TG, TC, LDL-C, HDL-C). Polysaccharide can not be digested in gastric and intestinal juice, but degraded into functional small molecules by gut microbiota in colon, exerting their activity in regulating glucose and lipid metabolism.…”
Section: Physiological Activities Of Glpmentioning
confidence: 99%